Pelatihan Pedagogik Guru dalam Menerapkan Pembelajaran Berbasis Blended Learning di SDN Siabu - Rani, Afriza Rahma; Fahrul, Yolanda; Aprinawati, Iis (Journal of Digital Community Services, 2024)
This dedication is motivated by the existence of elementary school teachers who still have difficulty implementing blended learning-based learning due to the teacher's lack of knowledge when creating blended learning-based lesson plans while the elementary school teacher has quite a long teaching experience. The teacher's pedagogical competence referred to in this devotionis the competence that the teacher has based on the teacher's teaching experience and the suitability of the teacher in implementing blended learning-based learning in the classroom. This devotionaims to describe quantitatively and qualitatively the pedagogical competence of teachers in implementing blended learning-based learning in elementary schools. These include: (1) teacher pedagogical abilities, (2) assessment of lesson plans using the Blended Learning Model, (3) Teacher Teaching Practices using the Blended Learning Model. The type of devotionused in this devotionis a mixed/combination type of devotionor what is usually called mixed methods sequential explanatory model. This devotionaims to measure and describe the pedagogical competence of elementary school (SD) teachers. The results of the devotionshowed that the teacher's pedagogical competency score was 60 in the sufficient category, in the assessment of the blended learning-based RPP it was 80 in the good category, while in the blended learning-based teaching practice it reached 84.5 in the good category. By conducting this research, a picture of teachers' pedagogical competence in blended learning-based learning at SDN 003 Siabu can be created. In this case, it is in line with the results of devotion(Trisno: 2012) which states that Pedagogical Competence is the ability to manage student learning which includes understanding students, designing and implementing learning, evaluating learning outcomes and developing students to provide variations in learning to reduce student boredom so that students focus. in learning stay focused.